A "plug-and-play" approach to the preparation of transparent luminescent hybrid materials based on poly(methyl methacrylate), a calix[4]arene cross-linking agent, and terbium ions - Driscoll, C.; Reid, B.; Mcildowie, Matthew; Muzzioli, S.; Nealon, Gareth; Skelton, B.; Stagni, S.; Brown, David; Massi, Massimiliano; Ogden, Mark (The Royal Society of Chemistry, 2011)
A novel methodology to prepare transparent luminescent hybrid materials is reported. Using a calixarene ionophore as a PMMA cross-linker avoids problems, such as phase segregation, andproduces a polymer monolith that can be loaded with the metal ion required for luminescence post-synthesis. This approach is versatile and will simplify the production of such materials.